2014
DOI: 10.1136/openhrt-2014-000154
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol increases patency and reduces adverse outcomes in percutaneous femoropopliteal revascularisation: a meta-analysis of randomised controlled trials

Abstract: BackgroundCilostazol is an oral antiplatelet agent currently indicated for treatment of intermittent claudication. There is evidence that cilostazol may reduce femoropopliteal restenosis after percutaneous endovascular intervention.MethodsWe searched PubMed, Scopus and Cochrane databases from 1966 through September 2013 for randomised controlled trials (RCTs) evaluating the addition of cilostazol to standard care in patients receiving femoropopliteal endovascular treatment. Restenosis, target lesion revascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…1 Recently, it has been shown that cilostazol reduces restenosis and target lesion revascularization after percutaneous transluminal angioplasty in patients with PAD as well. 10 Warner et al 38 have concluded that the addition of cilostazol after peripheral vascular interventions reduces the amputation rate and improves major outcomes. Consequently, cilostazol is recommended as a class 1 drug for patients with PAD according to the American Heart Association guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recently, it has been shown that cilostazol reduces restenosis and target lesion revascularization after percutaneous transluminal angioplasty in patients with PAD as well. 10 Warner et al 38 have concluded that the addition of cilostazol after peripheral vascular interventions reduces the amputation rate and improves major outcomes. Consequently, cilostazol is recommended as a class 1 drug for patients with PAD according to the American Heart Association guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol, a cyclic adenosine monophosphate phosphodiesterase inhibitor, has been introduced as a new antiplatelet agent due to its pleiotropic actions, including vasodilation and inhibition of platelet aggregation. [7][8][9] It has been demonstrated that cilostazol reduces in-stent restenosis (ISR) after coronary artery stenting 10 as well as after endovascular procedures for peripheral artery disease. 11 Several studies have also highlighted the superiority of this agent compared with other antiplatelet drugs concerning the secondary prevention of strokes as well as the protection against hemorrhagic events.…”
Section: Introductionmentioning
confidence: 99%
“…Cilostazol treatment has been routinely applied in patients with PAOD and DM to improve intermittent claudication and increase their walking distance. Additionally, recent papers have suggested that cilostazol treatment may improve stent patency in coronary arteries or peripheral arteries [16][17][18][19][20]. To the best of our knowledge, information regarding the clinical outcomes of cilostazol treatment in the management of CLI is limited.…”
Section: Introductionmentioning
confidence: 99%
“…27e29 A meta-analysis including 396 patients randomized to receive cilostazol plus antiplatelet treatment versus antiplatelet treatment alone, after a lower limb revascularization, with a follow-up from 12 to 24 months, has shown that cilostazol has efficiently and significantly reduced the restenosis incidence (À20%; P < 0.0001) and the need for repeat revascularization (À17%; P < 0.0001). 13 Another meta-analysis including more than 1,500 patientsdenrolled in 2 randomized studies and 4 prospective observational studiesdtreated with cilostazol plus antiplatelet treatment versus standard antiplatelet treatment alone, after a lower limb revascularization and with a follow-up from 18 to 37 months, has shown that cilostazol has efficiently and significantly reduced restenosis incidence (À29%; P < 0,001), decreased limb amputation (À58%; P < 0.001), and increased survival without any new revascularization procedures (+36%; P < 0.001). 14 Both studies have confirmed a satisfactory drug safety profile.…”
Section: Peripheral Revascularizationmentioning
confidence: 99%